Evaluasi Kelayakan Usaha Katering Makanan Sehat pada Dhaharan Indonesia di Masa Pandemic Ditinjau dari Aspek Keuangan - Nurfahmi Fadlillah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
TThe evaluation of business feasibility in the financial aspect is necessary to assess the feasibility of the UMKM Dhaharan Indonesia business in Desa Debong Wetan, Kec. Dukuhturi, Kab. Tegal. The objective of this study is to evaluate the feasibility of the UMKM Dhaharan Indonesia business using three methods: the cost ratio, which has a value of 1.36 > 1 (feasible to continue); the benefit-cost ratio, which has a value of 0.37 < 1 (not feasible to continue); and the break-even point, which amounts to Rp 25,535,714. According to the research results, UMKM Dhaharan Indonesia generated a total revenue of Rp 15,000,000 in June 2024, with a production cost of Rp 10,953,000, resulting in a profit of Rp 4,047,000.